Determinants of Depression Levels in Breast Cancer Survivors - Widodo, Dyah; Djuwadi, Ganif; DK, Farida Halis; Budianto, Bachtiar (Universitas Muhammadiyah Yogyakarta, 2024)
Background: Breast cancer is one type of malignancy in breast tissue that is experienced by many women throughout the world, including in Indonesia. Breast cancer shows high morbidity and mortality rates. The East Java Provincial Health Office noted that breast cancer cases have increased from year to year. The conditions and the process of cancer treatment can lead to psychological problems, including depression.Objective: This research aims to analyze the determinant factors that influence depression levels in breast cancer survivors.Methods: This study utilized the correlation method. The study was conducted in East Java. 158 respondents were selected using a purposive sampling technique. The instrument used in this research was a questionnaire that has been tested for validity and reliability. The data collection method used was face-to-face. Data analysis was carried out using SPSS software, including cross-tabulation and multivariate linear regression test with alpha 0.05.Results: Research findings show that marital status (p=0.021) is related to social support (p=0.002), physical condition (p=0.003), and the level of depression, but there was no relationship between age (p=0.281), the level of education (p=0.752) and the length of illness (p=0.265) and depression levels in breast cancer survivors.Conclusion: It is concluded that the determinants of factors that influence the level of depression are marital status, social support, and physical condition in survivors of breast cancer. Breast cancer survivors are expected to maintain their enthusiasm and not give up to avoid depression, which can reduce their health status.